Levormeloxifene - a non-hormonal woman-centric oral contraceptive under development: a comprehensive review - Singh, Man Mohan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The drugs controller general of India (DCGI) has granted permission to Cipla Limited, an Indian pharmaceutical company, to conduct Phase-I clinical trial of levormeloxifene for development as oral contraceptive for women as joint collaboration with CSIR-Central Drug Research Institute, Lucknow, India (CSIR-CDRI). Levormeloxifene is laevorotatory enantiomer of ormeloxifene, a benzopyran Selective Estrogen Receptor Modulator (SERM). Ormeloxifene is racemic mixture in equal quantities of levo- and dextro-enantiomers (compounds having same chemical composition but mirror-image 3-dimensional structures). In rats, levormeloxifene [Minimum Effective Dose (MED): 0.15 mg/kg/day] prevented pregnancy at almost half the dose than ormeloxifene (MED: 0.25 mg/kg/day) when administered orally covering the entire pre-implantation period. Levormeloxifene is equally effective as single 1 mg/kg dose when administered within 24 hours of coitus. In accordance with its higher relative binding affinity (RBA: 15.7±3.1 percent of estradiol-17β), levormeloxifene exhibited more potent estrogenic and antiestrogenic activities than the d-ormeloxifene (RBA: 2.10±0.9) or dl-ormeloxifene (RBA: 5.24±1.45). Besides, it shows promise in prevention of increased bone turnover and destructive joint diseases, and beneficial effect on serum lipids. This is the first comprehensive review providing relevant published information on structure, pharmaceutical properties, preparation, safety, pharmacokinetics and pharmacodynamics of levormeloxifene.